Study on effect of community service experience toward self-esteem among government employees at Pejabat Daerah dan Tanah Rompin, Pahang / Enur Eda Artikah Mat Hasani - Mat Hasani, Enur Eda Artikah (2013)
The aim of this study is to identify the effect of community service experience toward self-esteem among government employees at Pejabat Daerah dan Tanah Rompin, Pahang. Community service is motivated by the need to help others on the local level (Scafidi, 2008). Moreover, self-esteem can be defined as the complication of feelings that guide behavior, influences attitudes, and drive motivation (Dedmond, 2009). The researchers used Luke Terrence Reed (2006) to identify the relationship community service experience toward self-esteem among respondents. Questionnaires were distributed to 124 respondents to Pejabat Daerah dan Tanah Rompin, Pahang. The study concluded that the finding are generally consistent with previous studies which supported that there is no significant relationship between community service experience toward self-esteem among government employees at Pejabat Daerah dan Tanah Rompin, Pahang. The recommendation for future researchers especially for the further research, incorporating a significantly larger sample to be undertaken seeking confirming the result of the study and also can attempt to conduct the study in different location.